Flue gas treatment process for realizing ultralow emission of industrial silicon flue gas
By combining the lower wet desulfurization method and the upper dry desulfurization method in the flue gas treatment, and waterproofing modification of the dry desulfurizer particles, the problems of poor desulfurization effect and high equipment maintenance in the prior art are solved, and a more efficient flue gas desulfurization effect is achieved.
Patent Information
- Application Number
- CN202411710415.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-27
AI Technical Summary
There is a lack of a process that can effectively combine wet desulfurization and dry desulfurization in the existing flue gas treatment technology, resulting in poor desulfurization effect, large space occupied by the equipment and high maintenance difficulty.
A flue gas treatment process is adopted, combining wet desulfurization of the lower layer and dry desulfurization of the upper layer, and wet desulfurization is sprayed downward through the spraying device to perform wet desulfurization, and a porous carrier is installed on the upper layer to fill with waterproof modified desulfurizer particles to achieve dry desulfurization.
The combination of wet desulfurization and dry desulfurization is realized, which improves the desulfurization effect, reduces the equipment space and maintenance difficulty, and ensures effective contact between the desulfurizer and sulfur dioxide gas.
Smart Images

Figure CN119633570A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flue gas treatment and relates to a flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas. Background Art
[0002] At present, the desulfurization processes used in the treatment of industrial silicon flue gas mainly include wet desulfurization and dry desulfurization. The desulfurization effect of the dry desulfurizer will be seriously reduced after absorbing water and wetting. Therefore, it is difficult to mix the two in actual use. If a single wet desulfurization or dry desulfurization is used, in order to achieve a good desulfurization effect, it is necessary to set up multiple dry desulfurization structures or wet desulfurization structures in the desulfurization tower, which occupies a large space and is difficult to disassemble and repair the equipment.
[0003] In summary, at present, there is a lack of a desulfurization process that combines wet desulfurization and dry desulfurization in flue gas treatment. Summary of the invention
[0004] The purpose of the present invention is to provide a flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas, thereby solving the problem of lack of a desulfurization process combining wet desulfurization and dry desulfurization in flue gas treatment.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas, including dust removal, desulfurization, and denitrification, wherein the desulfurization includes lower layer wet desulfurization and upper layer dry desulfurization;
[0007] The lower layer wet desulfurization comprises the following steps: a flow equalizing plate is installed at a position near the bottom flue gas inlet of the desulfurization tower, a spray device is installed above the flow equalizing plate, an alkaline aqueous solution is sprayed downward by the spray device, and the flue gas from bottom to top in the desulfurization tower is countercurrently mixed with the alkaline aqueous solution from top to bottom to perform the lower layer wet desulfurization;
[0008] The upper layer dry desulfurization includes the following steps: a porous carrier is installed inside the desulfurization tower above the spray device, and the porous carrier is evenly filled with desulfurizer particles with a surface modified for waterproofing. The porous carrier is located above the spray device, and the flue gas from bottom to top in the desulfurization tower passes through the porous carrier after passing through the lower layer wet desulfurization for upper layer dry desulfurization.
[0009] The present invention performs waterproof modification on desulfurizer particles used in dry desulfurization, so that water mist in flue gas after wet desulfurization cannot affect the desulfurizer of dry desulfurization, realizing the combined use of wet desulfurization and dry desulfurization, and having a better desulfurization effect than the existing single wet desulfurization or dry desulfurization; and after the present invention performs waterproof modification on the desulfurizer of dry desulfurization, the waterproof layer formed on the surface of the desulfurizer particles has good air permeability and does not affect the contact between the desulfurizer and sulfur dioxide gas.
[0010] Furthermore, the waterproof modified desulfurizer particles are prepared by the following method:
[0011] S1. Add ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, methyl methacrylate and n-dodecyl mercaptan to hydrofluoroether, mix evenly and heat to 70° C. under stirring, add diisopropyl peroxydicarbonate at 70° C., continue stirring and react at 70° C. for 12 hours, let stand for 5 hours, wash and dry to obtain a first intermediate;
[0012] S2, melt-blending the first intermediate, the biodegradable polymer, and the photodegradable polymer, adding di-tert-butyl peroxide and sodium bicarbonate at 80° C., stirring and reacting for 2 hours, then cooling the reaction system to 60° C., adding cerium stearate at 60° C., mixing and stirring for 20-25 minutes to obtain a second intermediate;
[0013] S3, preparing desulfurizer particles: mixing mesoporous silica, activated carbon, alumina and calcium carbonate and stirring evenly to obtain a desulfurizer mixture, then slowly pouring the desulfurizer mixture into the silicone pressure-sensitive adhesive solution under stirring, stirring continuously at 50° C. and a stirring speed of 700 rpm for 20 minutes, granulating and drying to obtain desulfurizer particles;
[0014] S4, adding desulfurizer particles, rice husk powder, and silane coupling agent to the second intermediate in sequence, reacting for 2 hours at a stirring speed of 800 rpm, and then filtering and drying to obtain waterproof modified desulfurizer particles.
[0015] After the desulfurization particles of the dry desulfurization of the present invention are waterproofed, a waterproof layer with good air permeability is formed on the surface of the desulfurization particles. In order to quickly remove the waterproof layer on the surface of the desulfurization particles when the desulfurization particles are desorbed, the present invention adds biodegradable polymers, photodegradable polymers, and rice husk powder, and the waterproof layer on the surface of the desulfurization particles can be quickly removed under certain conditions such as light and microorganisms.
[0016] Furthermore, the porous carrier is a microsphere silica gel carrier.
[0017] Further, the biodegradable polymer comprises polylactic acid, carboxymethyl cellulose, and PBAT in a mass ratio of 1:1:1;
[0018] The photodegradable polymer is at least one of ethylene-carbon monoxide copolymer, vinyl ketone-ethylene copolymer, copolymer of propylene, vinyl chloride, styrene and vinyl ketone.
[0019] Furthermore, the mass ratio of the ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, and methyl methacrylate is 2:1:1; the amount of n-dodecyl mercaptan added is 1% of the total mass of ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, and methyl methacrylate; the amount of diisopropyl peroxydicarbonate added is 2% of the total mass of ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, and methyl methacrylate;
[0020] The mass ratio of the first intermediate, the biodegradable polymer, and the photodegradable polymer is 2:1.5:1, the amount of di-tert-butyl peroxide added is 1.5% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, the amount of sodium bicarbonate added is 0.6% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, and the amount of cerium stearate added is 1.6% of the mass of the photodegradable polymer;
[0021] The mass ratio of the mesoporous silica, activated carbon, alumina and calcium carbonate is 3:2:1:3;
[0022] The amount of rice husk powder added is 3% of the total weight of the first intermediate, the biodegradable polymer, and the photodegradable polymer;
[0023] The amount of silane coupling agent added is 0.8% of the mass of the desulfurizer particles.
[0024] Furthermore, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0025] Furthermore, the organic silicone pressure-sensitive adhesive is a methylsiloxane-type organic silicone pressure-sensitive adhesive.
[0026] Furthermore, the alkaline aqueous solution is aqueous ammonia or sodium hydroxide solution.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. A flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas. The desulfurizer particles used in dry desulfurization are modified to be waterproof, so that the water mist in the flue gas after wet desulfurization cannot affect the desulfurizer of dry desulfurization, and the combined use of wet desulfurization and dry desulfurization is achieved, which has a better desulfurization effect than the existing single wet desulfurization or dry desulfurization;
[0029] 2. After the desulfurizer for dry desulfurization is waterproofed by the present invention, the waterproof layer formed on the surface of the desulfurizer particles has good air permeability and does not affect the contact between the desulfurizer and sulfur dioxide gas;
[0030] 3. In order to quickly remove the waterproof layer on the surface of the desulfurization particles when the desulfurization particles are desorbed, the present invention adds biodegradable polymers, photodegradable polymers, and rice husk powder. Under certain conditions such as light and microorganisms, the waterproof layer on the surface of the desulfurization particles can be quickly detached. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which:
[0032] Figure 1 It is a SEM picture of the dry desulfurization agent particles after waterproofing of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0034] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0035] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0036] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0037] Example 1
[0038] A preferred embodiment of the present invention provides a flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas, including dust removal, desulfurization, and denitrification, wherein the desulfurization includes lower layer wet desulfurization and upper layer dry desulfurization;
[0039] The lower layer wet desulfurization comprises the following steps: a flow equalizing plate is installed at a position near the bottom flue gas inlet of the desulfurization tower, a spray device is installed above the flow equalizing plate, an alkaline aqueous solution is sprayed downward by the spray device, and the flue gas from bottom to top in the desulfurization tower is countercurrently mixed with the alkaline aqueous solution from top to bottom to perform the lower layer wet desulfurization;
[0040] The upper layer dry desulfurization includes the following steps: a porous carrier is installed inside the desulfurization tower above the spray device, and the porous carrier is evenly filled with desulfurizer particles with a surface modified for waterproofing. The porous carrier is located above the spray device, and the flue gas from bottom to top in the desulfurization tower passes through the porous carrier after passing through the lower layer wet desulfurization for upper layer dry desulfurization.
[0041] The waterproof modified desulfurizer particles are prepared by the following method:
[0042] S1. Add ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, methyl methacrylate and n-dodecyl mercaptan to hydrofluoroether, mix evenly and heat to 70° C. under stirring, add diisopropyl peroxydicarbonate at 70° C., continue stirring and react at 70° C. for 12 hours, let stand for 5 hours, wash and dry to obtain a first intermediate;
[0043] S2, melt-blending the first intermediate, the biodegradable polymer, and the photodegradable polymer, adding di-tert-butyl peroxide and sodium bicarbonate at 80° C., stirring and reacting for 2 hours, then cooling the reaction system to 60° C., adding cerium stearate at 60° C., mixing and stirring for 20-25 minutes to obtain a second intermediate;
[0044] S3, preparing desulfurizer particles: mixing mesoporous silica, activated carbon, alumina and calcium carbonate and stirring evenly to obtain a desulfurizer mixture, then slowly pouring the desulfurizer mixture into the silicone pressure-sensitive adhesive solution under stirring, stirring continuously at 50° C. and a stirring speed of 700 rpm for 20 minutes, granulating and drying to obtain desulfurizer particles;
[0045] S4, adding desulfurizer particles, rice husk powder, and silane coupling agent to the second intermediate in sequence, reacting for 2 hours at a stirring speed of 800 rpm, and then filtering and drying to obtain waterproof modified desulfurizer particles.
[0046] The porous carrier is a microsphere silica gel carrier.
[0047] The biodegradable polymer includes polylactic acid, carboxymethyl cellulose, and PBAT in a mass ratio of 1:1:1;
[0048] The photodegradable polymer is an ethylene-carbon monoxide copolymer.
[0049] The mass ratio of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate is 2:1:1; the amount of n-dodecyl mercaptan added is 1% of the total mass of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate, and the amount of diisopropyl peroxydicarbonate added is 2% of the total mass of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate;
[0050] The mass ratio of the first intermediate, the biodegradable polymer, and the photodegradable polymer is 2:1.5:1, the amount of di-tert-butyl peroxide added is 1.5% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, the amount of sodium bicarbonate added is 0.6% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, and the amount of cerium stearate added is 1.6% of the mass of the photodegradable polymer;
[0051] The mass ratio of the mesoporous silica, activated carbon, alumina and calcium carbonate is 3:2:1:3;
[0052] The amount of rice husk powder added is 3% of the total weight of the first intermediate, the biodegradable polymer, and the photodegradable polymer;
[0053] The amount of silane coupling agent added is 0.8% of the mass of the desulfurizer particles.
[0054] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0055] The organic silicone pressure-sensitive adhesive is a methylsiloxane-type organic silicone pressure-sensitive adhesive.
[0056] The alkaline aqueous solution is aqueous ammonia.
[0057] The SEM image of the desulfurizer particles after waterproofing in this embodiment is as follows: Figure 1 As shown, there is obvious stratification inside and outside.
[0058] Example 2
[0059] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the photodegradable polymer is ketene-ethylene copolymer.
[0060] Example 3
[0061] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the photodegradable polymer is a copolymer of propylene, vinyl chloride, styrene and vinyl ketone.
[0062] Example 4
[0063] This embodiment is based on Embodiment 1, but differs from Embodiment 1 in that the photodegradable polymer includes a copolymer of ethylene-carbon monoxide copolymer, ketene-ethylene copolymer, propylene, vinyl chloride, styrene and vinyl ketone, and the mass ratio of the copolymer of ethylene-carbon monoxide copolymer, ketene-ethylene copolymer, propylene, vinyl chloride, styrene and vinyl ketone is 1:1:1.
[0064] Example 5
[0065] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the alkaline aqueous solution is a sodium hydroxide solution.
[0066] Comparative Example 1
[0067] In this comparative example, only wet desulfurization is used during desulfurization, and the wet desulfurization includes the following steps: a flow equalizing plate is installed at a position near the bottom flue gas inlet inside the desulfurization tower, and a layer of spraying device is installed above the flow equalizing plate. An alkaline aqueous solution is sprayed downward by the spraying device, and the flue gas from bottom to top in the desulfurization tower is countercurrently mixed with the alkaline aqueous solution from top to bottom to carry out wet desulfurization, and the alkaline aqueous solution is ammonia water.
[0068] Comparative Example 2
[0069] In this comparative example, only dry desulfurization is used during desulfurization. The desulfurizer particles in the dry desulfurization are not subjected to waterproofing treatment. The desulfurizer particles are a mixture of mesoporous silica, activated carbon, alumina and calcium carbonate.
[0070] Comparative Example 3
[0071] Based on Example 1, the desulfurizer particles used in the dry desulfurization in this comparative example are not modified to be waterproof, and a mixture of mesoporous silica, activated carbon, alumina and calcium carbonate is placed on a carrier.
[0072] Comparative Example 4
[0073] Based on Example 1, no biodegradable polymer is added to the dry desulfurization agent particles of this comparative example during water-proof modification.
[0074] Comparative Example 5
[0075] Based on Example 1, the dry desulfurization agent particles of this comparative example do not add photodegradable polymer when performing waterproof modification.
[0076] Comparative Example 6
[0077] Based on Example 1, cerium stearate is not added to the dry desulfurization agent particles of this comparative example during water-proof modification.
[0078] Comparative Example 7
[0079] Based on Example 1, sodium bicarbonate is not added to the dry desulfurization agent particles of this comparative example during water-proof modification.
[0080] Comparative Example 8
[0081] Based on Example 1, the dry desulfurization agent particles in this comparative example are not added with silicone pressure-sensitive adhesive during waterproof modification.
[0082] Test Example 1
[0083] The desulfurization efficiency of Examples 1-5 and Comparative Examples 1-8 was measured. The results are shown in Table 1.
[0084] The calculation formula for desulfurization efficiency is: Desulfurization efficiency (m) = (SO2 mass concentration in the flue gas before the desulfurization tower × flue gas flow rate before the desulfurization tower - SO2 mass concentration in the flue gas after the desulfurization tower × flue gas flow rate after the desulfurization tower) / (SO2 mass concentration in the flue gas before the desulfurization tower × flue gas flow rate before the desulfurization tower) × 100%.
[0085] The method for detecting the flue gas desulfurization efficiency refers to the above calculation formula, which is a prior art and will not be elaborated in detail here.
[0086] Table 1 Desulfurization efficiency test results
[0087]
[0088] The desulfurization efficiency of the present invention is much higher than that of single dry desulfurization and wet desulfurization.
[0089] Test Example 2
[0090] The air permeability and water resistance of the 0.4 mm thin film formed from the second intermediate in Examples 1-5 and Comparative Examples 4-7 were measured, and the results are shown in Table 2. Sulfur dioxide was used as the detection gas when testing the air permeability of the film.
[0091] The calculation method of gas permeability is: G = V / A*t*P, where G represents the permeability, V represents the volume of the gas, A represents the area of the permeated film, t represents the thickness of the permeated material, and P represents the pressure of the gas at a certain temperature. It is expressed as the volume value at standard temperature and pressure, and the unit is cm 3 / (m 2 ·24h·0.1MPa). The gas permeability detection method is a prior art and will not be elaborated in detail here.
[0092] Waterproofness: Determine the water vapor transmission rate using the existing technology, with the unit being 1g / m 2 .day.1atm.
[0093] Table 2 Air permeability and waterproof test results
[0094] Breathability Waterproof Example 1 More than 50 Less than 1 Example 2 More than 50 Less than 1 Example 3 More than 50 Less than 1 Example 4 More than 50 Less than 1 Example 5 More than 50 Less than 1 Comparative Example 4 Less than 50 Greater than 1 Comparative Example 5 Less than 50 Greater than 1 Comparative Example 6 More than 50 Less than 1 Comparative Example 7 Less than 50 Less than 1
[0095] The waterproof layer coated on the outside of the dry desulfurization particles of the present invention has high air permeability and good waterproofness.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A flue gas treatment process for achieving ultra-low emissions of industrial silicon flue gas, including dust removal, desulfurization, and denitrification, characterized in that: The desulfurization includes lower layer wet desulfurization and upper layer dry desulfurization; The lower layer wet desulfurization comprises the following steps: a flow equalizing plate is installed at a position near the bottom flue gas inlet of the desulfurization tower, a spray device is installed above the flow equalizing plate, an alkaline aqueous solution is sprayed downward by the spray device, and the flue gas from bottom to top in the desulfurization tower is countercurrently mixed with the alkaline aqueous solution from top to bottom to perform the lower layer wet desulfurization; The upper layer dry desulfurization includes the following steps: a porous carrier is installed inside the desulfurization tower above the spray device, and the porous carrier is evenly filled with desulfurizer particles with a surface modified for waterproofing. The porous carrier is located above the spray device, and the flue gas from bottom to top in the desulfurization tower passes through the porous carrier after passing through the lower layer wet desulfurization for upper layer dry desulfurization.
2. The flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 1, characterized in that: The waterproof modified desulfurizer particles are prepared by the following method: S1. Add ethyl acrylate (N-methylperfluorohexylsulfonamide), butyl acrylate, methyl methacrylate and n-dodecyl mercaptan to hydrofluoroether, mix evenly and heat to 70° C. under stirring, add diisopropyl peroxydicarbonate at 70° C., continue stirring and react at 70° C. for 12 hours, let stand for 5 hours, wash and dry to obtain a first intermediate; S2, melt-blending the first intermediate, the biodegradable polymer, and the photodegradable polymer, adding di-tert-butyl peroxide and sodium bicarbonate at 80° C., stirring and reacting for 2 hours, then cooling the reaction system to 60° C., adding cerium stearate at 60° C., mixing and stirring for 20-25 minutes to obtain a second intermediate; S3, preparing desulfurizer particles: mixing mesoporous silica, activated carbon, alumina and calcium carbonate and stirring evenly to obtain a desulfurizer mixture, then slowly pouring the desulfurizer mixture into the silicone pressure-sensitive adhesive solution under stirring, stirring continuously at 50° C. and a stirring speed of 700 rpm for 20 minutes, granulating and drying to obtain desulfurizer particles; S4, adding desulfurizer particles, rice husk powder, and silane coupling agent to the second intermediate in sequence, reacting for 2 hours at a stirring speed of 800 rpm, and then filtering and drying to obtain waterproof modified desulfurizer particles.
3. The flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 1, characterized in that: The porous carrier is a microsphere silica gel carrier.
4. The flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 2, characterized in that: The biodegradable polymer includes polylactic acid, carboxymethyl cellulose, and PBAT in a mass ratio of 1:1:1; The photodegradable polymer is at least one of ethylene-carbon monoxide copolymer, vinyl ketone-ethylene copolymer, copolymer of propylene, vinyl chloride, styrene and vinyl ketone.
5. A flue gas treatment process for achieving ultra-low emissions of industrial silicon flue gas according to claim 4, characterized in that: The mass ratio of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate is 2:1:1; the amount of n-dodecyl mercaptan added is 1% of the total mass of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate, and the amount of diisopropyl peroxydicarbonate added is 2% of the total mass of (N-methylperfluorohexylsulfonamide) ethyl acrylate, butyl acrylate and methyl methacrylate; The mass ratio of the first intermediate, the biodegradable polymer, and the photodegradable polymer is 2:1.5:1, the amount of di-tert-butyl peroxide added is 1.5% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, the amount of sodium bicarbonate added is 0.6% of the total mass of the first intermediate, the biodegradable polymer, and the photodegradable polymer, and the amount of cerium stearate added is 1.6% of the mass of the photodegradable polymer; The mass ratio of the mesoporous silica, activated carbon, alumina and calcium carbonate is 3:2:1:3; The amount of rice husk powder added is 3% of the total weight of the first intermediate, the biodegradable polymer, and the photodegradable polymer; The amount of silane coupling agent added is 0.8% of the mass of the desulfurizer particles.
6. A flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 5, characterized in that: The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
7. A flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 2, characterized in that: The organic silicone pressure-sensitive adhesive is a methylsiloxane-type organic silicone pressure-sensitive adhesive.
8. The flue gas treatment process for achieving ultra-low emission of industrial silicon flue gas according to claim 1, characterized in that: The alkaline aqueous solution is ammonia water or sodium hydroxide solution.
Citation Information
Patent Citations
Disposable degradable material produced by using residual active sludge and preparation method thereof
CN102079851A
Activated carbon-based catalytic flue gas deep desulfurization device
CN112495183A
Granular desulfurizer and preparation method thereof
CN117919924A
Semi-dry desulfurization system
CN118142334A
Wet flue gas desulfurization dust collector
CN205550020U